IN VITRO EVALUATION OF NEWER FUNGICIDES AND BIOCONTROL AGENTS AGAINST CHILLI DAMPING OFF (Journal of Plant Disease Sciences, 2025)
Chilli (Capsicum annuum L.) is one of the most widely grown vegetable crops and is extensively used as a spice crop throughout the world. The chilli crop is affected by several diseases such as damping-off, wilt, anthracnose, die-back, root rot and bacterial wilt. Among the fungal diseases, damping-off caused by Pythium aphanidermatum (Edson) Fitzp. in nurseries is a major constraint in chilli production, resulting in up to 62% seedling mortality and accounting for nearly 90% plant death either as pre- or post-emergence damping-off under nursery conditions.Traditionally, the disease is managed using synthetic fungicides such as metalaxyl and carbendazim; however, their repeated use often leads to phytotoxicity and environmental concerns. This has created a need to evaluate newer fungicide formulations and eco-friendly alternatives for effective disease management. The present study was undertaken to evaluate the efficacy of newer fungicides and biocontrol agents against chilli damping-off disease. The results revealed that Metalaxyl-M 4% + Mancozeb 64% WP, Trifloxystrobin 25% + Tebuconazole 50% WG, and Mancozeb 64% + Cymoxanil 8% WP were the most effective treatments, showing 100% inhibition of the pathogen at the recommended concentration. Among the biocontrol agents tested, Bacillus subtilis and Pseudomonas fluorescens showed the highest antagonistic activity against the pathogen, recording 71.30% and 68.52% inhibition, respectively. The study indicates that newer fungicide combinations and selected biocontrol agents can be effectively utilized for managing damping-off disease of chilli in an eco-friendly and sustainable manner.
Keywords: Biocontrol, Chilli, Damping off, Fungicides, Pythium